Encyclopedia of solid-liquid interfaces - Wandelt, K. (Klaus), 1944-; Bussetti, Gianlorenzo (Elsevier, 2024)
"Encyclopedia of Solid-Liquid Interfaces is designed to provide a comprehensive overview of macroscopic phenomena at solid-liquid interfaces, e.g. in physics, chemistry, geology, biology and technology, and to describe the methodological approaches and strategies to gain microscopic insight into the underlying properties and processes on the atomic/molecular level. Covering an area of chemistry that plays a fundamental role in nature and technology, the book compiles all relevant features of the field into a 'one-stop' reference source that will be relevant to a wide range of interdisciplinary scientists, researchers and academics. Encompassing 170 chapters by renowned experts, and led by leading names in the field, the contents will be organized over 3 volumes."--Publisher's website.